2012
DOI: 10.1186/1756-0500-5-344
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of maximal strength training on walking efficiency in patients with schizophrenia – a pilot study

Abstract: BackgroundPatients with schizophrenia frequently have disabling gait deficits. The net mechanical efficiency of walking (ϵnet) is an accurate measure often used to evaluate walking performance. Patients with gait deficits have a reduced ϵnet with excessive energy expenditure during sub-maximal walking. Maximal strength training (MST) improves ϵnet in healthy individuals and is associated with reduced risk of mortality. The aim of this study was to investigate whether MST improves ϵnet in patients with schizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 21 publications
(38 reference statements)
5
65
1
Order By: Relevance
“…While the importance of neural factors in strength training in the elderly population should yet be treated with some caution because of the low sample size and limited muscle groups studied in the current study, recommendations of heavy resistance training with emphasis on maximal mobilization in the concentric phase has provided excellent results not only in this study, but in a wide range of untrained patient populations (de Vos et al 2005;Hoff et al 2007;Caserotti et al 2008;Husby et al 2009;Fimland et al 2010;Fimland et al 2011;Heggelund et al 2012;Hill et al 2012;Mosti et al 2013). Although the isometric training may also account for some of the adaptations, these studies together present mounting evidence that heavy resistance training not only is feasible and effective; additionally, no incidents of injury have been reported.…”
Section: Heavy Resistance Training In Elderly: Clinical Implicationsmentioning
confidence: 92%
“…While the importance of neural factors in strength training in the elderly population should yet be treated with some caution because of the low sample size and limited muscle groups studied in the current study, recommendations of heavy resistance training with emphasis on maximal mobilization in the concentric phase has provided excellent results not only in this study, but in a wide range of untrained patient populations (de Vos et al 2005;Hoff et al 2007;Caserotti et al 2008;Husby et al 2009;Fimland et al 2010;Fimland et al 2011;Heggelund et al 2012;Hill et al 2012;Mosti et al 2013). Although the isometric training may also account for some of the adaptations, these studies together present mounting evidence that heavy resistance training not only is feasible and effective; additionally, no incidents of injury have been reported.…”
Section: Heavy Resistance Training In Elderly: Clinical Implicationsmentioning
confidence: 92%
“…Muscle strength maintenance is the basis for preserving functionality and independence in activities of daily living. 10,36 A cohort study of 8,762 men aged 20 to 80 years showed that maximum force is independently and inversely associated with all-cause mortality. 37 A resistance or concurrent training program might improve muscle strength and function.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that patients with schizophrenia can safely participate in and benefit from resistance training; furthermore, the program did improve the mechanical efficiency of walking. 10 Serum BDNF and IGF-1 levels were measured as possible biomarkers of the neurobiological mechanisms of improvement or maintenance of schizophrenia symptoms thorough the exercise intervention. These trophic factors are the most commonly used biomarkers for this purpose, and play a critical role in signaling between various tissues, especially in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Jorn Heggelund et al [40] found that patients with schizophrenia may participate of a secure program of maximum strength training, resulting in an improvement in physical health. In this study of 16 patients, 9 were assigned to the experimental group and 7 for the control group.…”
Section: Effects Of Exercise On Physical Health In Schizophreniamentioning
confidence: 99%